NBOMes–Highly Potent and Toxic Alternatives of LSD - Zawilska, Jolanta B.; Kacela, Monika; Adamowicz, Piotr (Frontiers in Neuroscience, 2020)
Recently, a new class of psychedelic compounds named NBOMe (or 25X-NBOMe) has appeared on the illegal drug market. NBOMes are analogs of the 2C family of phenethylamine drugs, originally synthesized by Shulgin, that contain a N-(2-methoxy)benzyl substituent. The most frequently reported drugs from this group are 25I-NBOMe, 25B-NBOMe and 25C-NBOMe. NBOMe compounds are ultrapotent and highly efficacious agonists of serotonin 5-HT2A and 5-HT2C receptors (Ki values in low nanomolar range), with more than 1000-fold selectivity for 5-HT2A compared with 5-HT1A. They display higher affinity for 5-HT2A receptors than their 2C counterparts and have markedly lower affinity, potency and efficacy at the 5-HT2B receptor compared to 5-HT2A or 5-HT2C. The drugs are sold as blotter papers, or in powder, liquid or tablet form, and administered sublingually/buccally, intravenously, via nasal insufflations or by smoking. Since their introduction in the early 2010s, numerous reports have been published on clinical intoxications and fatalities resulting from the consumption of NBOMe compounds. Commonly observed adverse effects include visual and auditory hallucinations, confusion, anxiety, panic and fear, agitation, uncontrollable violent behavior, seizures, excited delirium and sympathomimetic signs such mydriasis, tachycardia, hypertension, hyperthermia and diaphoresis. Rhabdomyolysis, disseminated intravascular coagulation, hypoglycemia, metabolic acidosis, and multiorgan failure were also reported. This survey provides an updated overview of the pharmacological properties, pattern of use, metabolism and desired effects associated with NBOMe use. Special emphasis is given to cases of non-fatal and lethal intoxication involving these compounds. As the analysis of NBOMes in biological materials can be challenging even for laboratories applying modern sensitive techniques, this paper also presents the analytical methods most commonly used for detection and identification of NBOMes and their metabolites.